What do they know, and what would they like to know? A study into information needs of dementia caregivers in Croatia (Libellarium: journal for research in the field of information and related sciences, 2023)
Purpose. The paper presents the findings of a study into the knowledge about dementia among the caregivers of people with dementia in Croatia, and their information needs.Methodology. The study was conducted on the sample of 53 participants, caregivers of people with dementia, in the period from September through November 2023. The datawere collected by means of an online survey that was distributed to the respondents via local Dementia.net Facebook page.Findings. The respondents believe that dementia caregivers in Croatia do not have adequate support and they are aware of their lack of knowledge about dementia. Most respondents require information about the rights and benefits of people with dementia and their families. Most often they obtain required information on social media and from other caregivers. Almost half of the respondents sought at least once dementia information in their local public library, and more than half think that caregivers in Croatia face many obstacles in obtaining required information.Practical implications. Since dementia caregivers do not know where to look for needed information and due to the lack of an adequate information support system they turn to informal sources of information. This study could motivate libraries to build dementia collections which would meet the identified information needs of people with dementia.Social implications. Dementia collections comprising popular fiction and picture books which are targeted at general population could facilitate the sensibilization of the public about the disease and the removal of social discrimination against people affected by dementia.Originality. This paper presents a valuable contribution to better understanding the dementia caregivers’ information needs in Croatia.
Keywords: caregivers; Croatia; dementia; information behaviour; information needs